Pengaruh Good Corporate Governance Terhadap Kinerja Perusahaan - Putri, Juliana; Syaiful, Syaiful (Universitas Muhammadiyah Gresik, 2025)
This study aims to prove the effect of good corporate governance as proxied through independent commissioners, institutional ownership, managerial ownership and audit committees on company performance by manufacturing companies listed on the Bursa Efek Indonesia in 2019-2021. The independent variables used are independent board of commissioners as measured by comparing the number of independent commissioners and the total number of commissioners, then institutional ownership as measured by comparing the number of shares owned by the institution and the number of shares outstanding, then managerial ownership as measured by comparing the number of shares managerial ownership and the number of shares outstanding, and the audit committee as measured by the number of audit committees. The dependent variable used is company’s performance as measured using the Return On Assets (ROA) by comparing the amount of net profit after tax and total assets. Test were carried out using SmartPLS. The results obtained from this study are the independent commissioners and the aduit committee have a significant effect on company performance, while institusinal ownership and managerial ownership have no significant effect on company performance.